STRUKTUR MUSIK IRINGAN TARI BAKONCONG PADA SUKU DAYAK BADAMEA DESA SENATAB KECAMATAN SAJINGAN BESAR KABUPATEN SANBAS - Toto, Widina Karma; Ismunandar, Ismunandar; Silaban, Chiristianly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis background of this researchers to find musical structures accompanied by Bakoncong dance of the Badamea Dayak tribe of Senatab Village, Sajingan Besar District, Sambas Regency. The problem of this research were "What is the structure of the accompaniment of Bakoncong dance of the Dayak Badamea tribe, The design of the implementation of the structure of music accompaniment to the Bakoncong dance in class VIII cultural arts subjects. This research method was an exploratory descriptive method. The form of this research was qualitative. The approach of this research was ethnomusicology approach. The data of this study were the results of interviews, observations, documentation. The data collection techniques of this study were observation, direct communication and documentary studies. The research data collection tool were the researcher as the main instrument, observation guidelines and documentation tools. Checking the validity of the research data were an extension of observation and triangulation of techniques. The data analysis technique of this research were the analysis during data collection analyzed after data collection. The results of this study were describing the accompaniment of music structure of Bakoncong dance, understanding of Bakoncong, and musical instrument. The design of the implementation of the accompaniment of music structures in the Bakoncong dance on class VIII cultural arts subjects.Â Keywords: Accompaniment music, Bakoncong dance, Structure of music.